2013
DOI: 10.1088/0953-8984/25/46/465701
|View full text |Cite
|
Sign up to set email alerts
|

Spin nutation effects in molecular nanomagnet–superconductor tunnel junctions

Abstract: Abstract. We study the spin nutation effects of the molecular nanomagnet on the Josephson current through a superconductor|molecular nanomagnet|superconductor tunnel junction. We explicitly demonstrate that due to the spin nutation of the molecular nanomagnet two oscillatory terms emerge in the ac Josephson current in addition to the conventional ac Josephson current. Some resonances occur in the junction due to the interactions of the transported quasiparticles with the bias voltage and molecular nanomagnet s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…14 The effects of molecular nanomagnet's spin nutation on the Josephson current flowing through the Josephson junction has been studied in Ref. 15. It has been shown that the spin nutation of the molecular nanomagnet causes generation of an ac Josephson current through the junction, in addition to the dc one.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…14 The effects of molecular nanomagnet's spin nutation on the Josephson current flowing through the Josephson junction has been studied in Ref. 15. It has been shown that the spin nutation of the molecular nanomagnet causes generation of an ac Josephson current through the junction, in addition to the dc one.…”
mentioning
confidence: 99%
“…is the real part of the retarded potential which is obtained using the Matsubara Green's functions and analytical continuation 14,15,28 as;…”
mentioning
confidence: 99%
See 1 more Smart Citation